Atividade antioxidante e hepatoprotetora de plantas brasileiras, contendo compostos fenólicos. - Sabir, Syed Mubashar (2010)
Plants from Brazilian flora were chosen and studied for their in vitro and in vivo antioxidant and in vivo hepatoprotetive activity, especially in relation to phenolic compounds which have several health benefits. These plants include Phyllanthus niruri, Solanum fastigiatum, Solidago microglossa and Baccharis trimera. The aqueous extracts of leaves showed inhibition against thiobarbituric acid reactive species (TBARS), induced by different pro-oxidants (10 μM FeSO4 and 5 μM sodium nitroprusside) in rat liver and brain homogenates. The extracts also lowered the formation of TBARS in phospholipid extracted from egg yolk. On the lipid peroxidation assay the order of antioxidant activity was Solidago microglossa>Phyllanthus niruri> Solanum fastigiatum> Baccharis trimera. The free radical scavenging activities of the extract were determined by the quenching of a stable 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical. The IC50 value of Solidago microglossa (3.8± 0.1 μg/ml), Phyllanthus niruri (43.4 ± 1.45 μg/ml), Solanum fastigiatum (68.96±1.25 μg/ml) and Baccharis trimera (415.2±15.2 μg/ml) indicates that the order of antioxidant activity is Solidago microglossa > Phyllantus niruri > Solanum fastigiatum > Baccharis trimera. The hepatoprotective activity of the extracts were also demonstrated in vivo against paracetamol-induced liver damage, as evidenced by the decrease in serum glutamate oxaloacetate transaminase (GOT), and glutamate pyruvate transaminase (GPT), and decreased catalase activity in the liver in treatment groups, compared to the control. The aqueous extract also showed significant (p<0.05) hepatoprotective activity that was evident by enzymatic examination and brought back the altered levels of TBARS, non-protein thiol and ascorbic acid to near the normal levels in a dose dependent manner. Acute toxicity studies of Solanum fastigiatum revealed that the LD50 value of the extract is more than the dose 4 g/kg body weight of mice whereas, the genotoxicity of Solidago microglossa was tested using comet assay. The results obtained on the comet assay revealed that under the experiment used the extract was not genotoxic to human lymphocytes at a relatively high concentration of 0.5 mg/ml. The content of phenolics was determined using Folin Ciocalteu,s assay. The phenolic content was found to be the highest in Solidago microglossa and the lowest in Baccharis trimera. Phytochemical analysis of these plants was carried out on the basis of TLC/HPLC. The TLC analysis showed the presence of rutin in aqueous extract of Phyllanthus niruri, while, Solanum fastigiatum showed the presence of rutin and quercetin. The Phenolic profile of Solidago microglossa and Baccharis trimera was determined by using High performance liquid chromatography. On the basis of the HPLC data, quercetin (254.88±5.1 μg/ml), rutin (342.2±7.1 μg/ml) and gallic acid (2320.8±13.2 μg/ml) have been identified and quantified in the ethanolic extract of Solidago microglossa. Whereas, HPLC analysis revealed the presence of gallic acid (76.8±7.2 μg/ml) as a major compound while, rutin (20.1±2.5 μg/ml) and quercetin (10.1±1.4 μg/ml) relatively showed minor contribution in the aqueous extract of Baccharis trimera. In conclusion, the crude extract of these plants showed high antioxidant and free radical scavenging activities which are related to the presence of phenolic compounds. These results may have implications in the use of the extracts as a therapeutic agent in the prevention of oxidative stress related diseases.